Development of Powtoon-Based Animated Videos to Improve Critical Thinking Skills Middel School Students In Science Learning - Teresa Dinasty Mulyana; Sri Wahyuni*; Rusdianto Rusdianto (Universitas Syiah Kuala, 2023)
The aim of this study was to develop the science learning media by using powtoon-based animated video that can be valid, practical and effective in order to build the students’ critical thingking in SMP Negeri 12 Jember. This study applied the ADDIE model that consist of analysis, design, development, implementation and evaluation method. The data used in this study was based on the research instruments including validation sheets, learning implementation sheets, questionnaires, and tests of students’ critical thingking. The research subjects were consist of 31 students of Class VIIIB at SMP Negeri 12 Jember. The result of this study showed that first the animated video has 90% validity score by the expert. Furthermore, this animation videos had 3.87 average of practicallity which can be categorized as practical and was carried out very clearly. For the effectiveness of the animated video achieved an N-gain of 0.92 that can be classified as high category. Finally, for the students’ respon from the questionnaires showed that 92% was categorized as very good. Based on the result can be concluded that the development of Powtoon-based animated video was effective in improving the students’ critical thingking